2021
DOI: 10.31234/osf.io/kgajv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is structural priming between different languages a learning effect? Modelling priming as error-driven implicit learning

Abstract: To test whether error-driven implicit learning can explain cross-language structural priming, we implemented three different models of bilingual sentence production: Spanish-English, verb-final Dutch-English, and verb-medial Dutch-English. With these models, we conducted simulation experiments that all revealed clear and strong cross-language priming effects.One of these experiments included structures with different word order between the two languages. This enabled us to distinguish between the error-driven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…If on the other hand combinatorial nodes are connected rather than shared between languages, betweenlanguage priming effects should be weaker than within-language priming effects (at least if one assumes the architecture of Pickering & Branigan, 1998: in which multiple verbs within a language share their combinatorial nodes), as priming resulting from the repeated use of one combinatorial node is stronger than priming resulting from co-activated nodes (due to activation loss between input and output nodes). Several studies found stronger within-language priming than between-language priming (e.g., Bernolet, Hartsuiker & Pickering, 2013;Cai, Pickering, Yan & Branigan, 2011), and a recent simulation model also suggested that this is the case (Khoe, Tsoukala, Kootstra & Frank, 2021).…”
Section: Bilingual Syntactic Representationsmentioning
confidence: 97%
“…If on the other hand combinatorial nodes are connected rather than shared between languages, betweenlanguage priming effects should be weaker than within-language priming effects (at least if one assumes the architecture of Pickering & Branigan, 1998: in which multiple verbs within a language share their combinatorial nodes), as priming resulting from the repeated use of one combinatorial node is stronger than priming resulting from co-activated nodes (due to activation loss between input and output nodes). Several studies found stronger within-language priming than between-language priming (e.g., Bernolet, Hartsuiker & Pickering, 2013;Cai, Pickering, Yan & Branigan, 2011), and a recent simulation model also suggested that this is the case (Khoe, Tsoukala, Kootstra & Frank, 2021).…”
Section: Bilingual Syntactic Representationsmentioning
confidence: 97%
“…For example, Kantola and Van Gompel (2011) found that the Swedish-English bilinguals in their study were primed at comparable rates in their English, irrespective of whether the prime was in their L1 (i.e., Swedish) or L2 (see also Hartsuiker, Beerts, Loncke, Desmet, & Bernolet, 2016;Schoonbaert et al, 2007). There are however several studies which have found stronger within-language than between-language priming (Bernolet et al, 2013;Khoe, Tsoukala, Kootstra, & Frank, 2021;Travis, Cacoullos, & Kidd, 2017). For example, Cai et al (2011) reported on two experiments with Cantonese-Mandarin bilinguals using the dative alternation.…”
Section: Shared Syntactic Representations and Structural Priming In B...mentioning
confidence: 99%